Mucormycosis of the Middle Ear and Neck Post COVID 19 - Dongol, Kripa; Rayamajhi, Pabina; Pradhananga, Rabindra Bhakta; Dulal, Malati; Sedhai, Milan; Gurung, Bikash (Journal of Nepal Health Research Council, 2023)
Mucormycosis is an opportunistic infection caused by fungi of order Mucorales and affect immunosuppressed patients. The cases of mucormycosis have surged during the COVID pandemic, especially in cases requiring steroids and mechanical ventilation. Here we present a case of a 40-year-old diabetic post COVID female patient. She presented with right earache, right facial paralysis (grade four) of two weeks duration and right sided neck swelling for ten days. Ultrasonography and computed tomography revealed multiple abscesses in the right side of the neck. Histopathological examination of tissue from the neck and middle ear confirmed the diagnosis of mucormycosis. This is a rare case of concurrent neck and middle ear mucormycosis in a post COVID patient.Keywords: Coronavirus; COVID 19; middle ear; mucormycosis; neck.